Kohesi Gramatikal dan Leksikal pada Podcast Anies Baswedan dan Drama Pilkada di Chanel Youtube Mata Najwa 2024 - Rossy Tiara Sahana; Atiqa Sabardila (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the forms of grammatical and lexical cohesion in the discourse contained in the Anies Baswedan Podcast and the Pilkada drama on the Mata Najwa YouTube channel. Cohesion analysis in discourse is important because it can reveal the integration of meaning, the relationship between sentences, and the language strategies used by the sources to build arguments and self-image. The research methods used are the distribution method and the equivalent method. The distribution method is used to analyze language structures internally, while the equivalent method, especially referential equivalents, is used to see the relationship between language elements and their references outside the language. The data source for this research is a podcast recording on the Mata Najwa YouTube channel that specifically discusses the topic of Anies Baswedan and the dynamics of the Pilkada drama. The object of study focuses on the interactive chat between Anies Baswedan and Najwa Shihab which contains various language strategies. The data collection technique was carried out using listening and note-taking techniques, assisted by advanced methods to ensure the accuracy of data identification. The results of the study show that there are 36 cohesion data divided into 17 grammatical cohesion data and 19 lexical cohesion data. The grammatical cohesion found includes the use of references (personal and demonstrative pronouns), substitution, conjunctions, and ellipsis that function to connect language elements syntactically. Meanwhile, lexical cohesion includes the use of synonyms, antonyms, repetitions, and hyponyms that build semantic integration of meaning. This study confirms that the existence of grammatical and lexical cohesion in oral discourse plays an important role in creating message integrity and clarifying the speaker's intent. In addition, this finding shows that the interaction in Mata Najwa is not only informative, but also rhetorical, where cohesion is used strategically to build political narratives and influence audience perceptions.